USING MOBILE LEGEND MEDIA IN PROCEDURE TEXT TO INCREASE STUDENTS WRITING SKILL AT GRADE IX OF SMP IT AL IKHWAN TANJUNG MORAWA ACADEMIC YEAR 2021/2022 - Debby Pratiwi; M. Khalid (Jurnal Inovasi Penelitian, 2022)
The purpose of this study was to determine whether there was a significant effect of using mobile legend media on procedure text to improve student's writing ability. This type of research is quantitative research and is carried out with an experimental design with two classes, namely the experimental class with 20 students and the control class with 20 students. In the data collection technique, the researcher conducted a pre-test, treatment and post-test by giving an essay test consisting of 10 questions. The results of this study indicate that there is a significant effect of using mobile legend media on procedure text. This can be seen from the difference in the average pre-test and post-test scores of students in the experimental class which increased from 61.5 to 79.5. The average pre-test score in the control class was 60.25 while the post-test average in the control class was 66.75. This means that mobile legend media in procedure text can be applied to improve students' writing skills.